DEVELOPMENT OF BUSINESS MANAGEMENT IN UZBEKISTAN (International journal of artificial intelligence, 2024)
The economy of Uzbekistan has been developing rapidly in recent years. A number of reforms are being implemented in the country in order to improve the business environment, attract investments and increase competitiveness. This article considers the main directions and important aspects of the development of business management in Uzbekistan.